Encouraging High School Student's Creative Thinking in Improving Speaking Skilll - Annisa Tiara Syafitri; Wijayadi Wijayadi; Pramudana Ihsan (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This research is based on learning that applies creative thinking skills in improving the speaking ability of high school students. the application of the 21st century in learning is stated to be very necessary and able to improve students' abilities in this modern era. Researchers describe the results and changes experienced by students before and after learning by applying creative thinking during class. The purpose of this research is to improve students' speaking skills to be better and fluent by applying creative thinking in every meeting and class learning. The researchers using qualitative descriptive data to explain the result and for the strategy researcher choose discovery learning by utilizing creative thinking consist of 25 students in a class. This methodology has several advantages including classroom action research which consists of planning and taking surveys through online data collection.the instrument will be collect from intervew and questionaire. Data analysis showed that most of the students in one class showed satisfactory results with a parameter which is an assessment table that in accordance with the abilities that must be achieved by students to make their speaking skill better. This is indicated by the increasing ability of students during the final test. The average score of students to be better 85% based on the calculation of the graph. Speaking skills such as pronunciation, vocabulary and intonation are getting better. During learning, students feel comfortable and enjoy. So, from the results obtained, it can be said that students' creative thinking is encouraged and their speaking skills are increased.. Key Words: Creative thinking, speaking skill